Penerapan Model Pembelajaran Discovery Learning Dalam Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Bilangan Bulat Kelas VII SMP Alwathan Ambon - Zurimi, Safarin; Basafin, Waonda; Hukunala, Mozard A.; K, Kasriana; D, Darwin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The application of discovery learning model in integer number material class VII SMP Alwathan Ambon. The research subjects were the seventh grade students of Alwathan Ambon Junior High School with a total of 30 students consisting of 16 boys and 14 girls. This research was conducted in class VII of Alwathan Ambon Junior High School on November 23 - December 23, 2022. This research is a quantitative descriptive research. Data analysis was processed using quantitative analysis to obtain the final score. The results of the study of students' cognitive scores before the application of the dicavery learning model found 5 students who were complete (17%), and those who were not complete were 25 students (83%). After applying the dicavery learning model, it can be seen that in cycle I there were 14 students who were complete (47%) and 16 students who were not complete (53%). In cycle II there were 28 students who were complete (93%) and 2 students who were not complete (7%). So the results showed that the discavery learning model can improve the learning outcomes of VII grade students of Alwathan Ambon Junior High School in the subject of integers.